Thermodynamic evaluation of a pumped thermal electricity storage system integrated with large-scale thermal power plants. (April 2023) - Blanquiceth, J.; Cardemil, J.M.; Henríquez, M.; Escobar, R.
Abstract: The use of renewable energies is an alternative for decarbonizing the electricity generation sector and thus large-scale energy storage systems are required. The purpose of the present study is to assess the performance of the emerging Pumped Thermal Electricity Storage (PTES) systems and their integration with thermal power plants (TPP). A suitable thermal storage system (TES) has been extensively studied and five alternatives for the simulation of two-tank molten salt storage are implemented. Several options for the charge and discharge systems are modeled. The Round-Trip-Efficiency (RTE) is evaluated and accompanied by the power and energy density. A sensitivity analysis is performed by varying the main operational parameters to evaluate different utilization scenarios. The results are compared with the reported performance of commercial systems. The RTE of the integrated PTES configurations is around 50%–65% and high values of energy and power density can be achieved. For Rankine cycle configurations, the argon heat pump is recommended. Reusing old coal power plants, while plausible for reducing costs, results in moderate RTEs. In modern supercritic Rankine cycles, the reachable RTE is greater than 63%. RTE in Brayton and air heat pump configurations is similar, especially over 700 °C at the discharge. However, it is highly sensitive to other operational parameters, and the energy density is significantly lower. Therefore, a more suitable TES system is required. Compared to commercial technologies, the system studied has the potential of being implemented if energy and power density are exploited to produce cost-effective systems. Highlights: A comprehensive methodology for the thermal integration of PTES systems is presented. Validation of the thermodynamic model of PTES systems against literature data. Evaluation considering key performance metrics associated to the size of PTES systems. Sensitivity analysis to identify optimum configurations for PTES systems. Comparison of the proposed PTES systems with commercial technologies is performed.